PENINGKATAN KECERDASAN INTERPERSONAL MELALUI PEMBELAJARAN KOOPERATIF - Yusdiana, Yusdiana (Jurnal Pendidikan Usia Dini, 2014)
Abstract: The objective of this research was to improve the interpersonal intelligences improveearly childhood learning cooperative at Kindergarten Asy-Syifa West Java city of Serang. Thedata were collected through participant observation using interview, observation, document study,and recording. The data analysis and interpretation indicates that: The results obtained showedthat the increase of 21,15%. In a quantitative comparison of child interpersonal intelligencesbefore and after the action. Informant Number 13; Raw Data Pretest Total Score 858; AverageClass Pretest 66; Raw Data posttest Total Score 1184; Average Class posttest 91.08. Based onthese results, the researchers suggest: 1) Teachers should create a conducive learning process,comfortable and fun, setting up media which aims to improve the interpersonal intelligencesconcept in concrete terms so that the child can be stimulated properly, 2) schools, better preparefacilities and varied infrastructure that supports interpersonal intelligences education so as toimprove social interaction, communication, socialization, empathy, and collaboration . Keywords: Interpersonal Intelligences, Cooperative Learning, Action Reacrh Abstrak: Tujuan dari penelitian ini untuk meningkatkan kecerdasan interpersonal melaluipembelajaran kooperatif di TK As-Syifa di Serang. Data yang dikumpulkan melalui observasipartisipan dengan wawancara, observasi, studi dokumentasi, dan video rekaman. Analisis data daninterpretasi menunjukkan bahwa hasil peningkatan sebesar 21,05%. Pada satu perbandingankwantitatif dari inteligen hubungan antar pribadi anak sebelum dan setelah aksi. Angka penuturasli 13; Data mentah Pretest Jumlah Score 858; Merata-ratakan Kelas Pretest 66; Data mentahpost test Jumlah Score 1184; Merata-ratakan Kelas posttest 91.08. Berlandaskan hasil ini,peneliti sarankan: (1) Guru harus menciptakan satu belajar mungkinkan berjalan, nyaman danceria, membuat media yang mana bertujuan meningkatkan inteligen hubungan antar pribadi anakdapat dirangsang dengan baik; (2) sekolah, persiapkan lebih baik fasilitas dan membedakaninfrastruktur dukungan itu untuk mendukung kecerdasan interpersonal untuk meningkatkaninteraksi sosial, komunikasi, sosialisasi, empati, dan kerjasama. Kata kunci: Kecerdasan Interpersonal, Pembelajaran Kooperatif, Penelitian Tindakan